Preface translation as a feminist and inclusive language usage action - Lima, Érica (Meta, 2022)
This paper focuses on the translation of a collection of seventeen prefaces for different editions of the book Our Bodies, Ourselves (Chatterjee 2008/2020, translated by Nicolella, Oliveira et al.). The translation project is part of a collective and voluntary translation agreement made between the State University of Campinas, the Federal University of Rio de Janeiro, and an NGO (Coletivo Feminista Sexualidade e Saúde) to translate and adapt to Brazilian Portuguese the widely known book Our Bodies, Ourselves (The Boston Women’s Health Book Collective 2011). Two points were discussed more thoroughly: first, the importance of paratexts (Genette 1987/1997) and paratranslation, especially the intersemiotic interpretation of the text and the image of the book cover (Yuste Frías 2022; 2021; 2011); and second, inclusive language use (Governo do Estado do Rio Grande do Sul 2014), considering that the masculine form is the standard in Portuguese while the translation project concerns a feminist book (Davis 2007). We present four examples of translations made by students with the support of CAT tools and revised considering a more inclusive language usage. In the final remarks, we will discuss that the translation project provided the integration between translation practice and theoretical discussions underlying this practice. We will also point out some challenges and discussions still ongoing in Brazil.